DEVELOPMENT OF BIOLOGY TEST OF CREATIVE THINKING-TORRANCE TEST (BTCT-TT) ASSESSMENT TO IMPROVE STUDENTS' CREATIVE THINKING SKILLS - Radiah (lppm Universitas Negeri Jakarta, 2020)
This research aims to developing the Biology Test of Creative Thunking-Torrance Test (BTCT-TT) assessment in studying Biology for high school student in grade 11. This type of research is Research& Development (R & D) with 4D (Define, Design, Develop, and Disseminate). This study have develodped 37 items that are valid and reliabel. BTCT-TT was tested on 150 high school students, the results showed the average score of students' creative thinking skills was significantly releted to students who received BTCT-TT assessment and Conventional assessment.   Keywords: Biology Test of Creative Thinking-Torrance Test (BTCT-TT), Creative Thinking